Highly reversible oxygen redox in layered compounds enabled by surface polyanions - Qing Chen (Nature Portfolio, 2020)
Oxygen-anion redox in lithium-rich layered oxides can boost the capacity of lithium-ion battery cathodes. Here, the authors investigate the mechanism of surface degradation caused by oxygen oxidation and the kinetics of surface reconstruction.